Violência como uma expressão da questão social: suas manifestações e seu enfrentamento no espaço escolar - Schmidt, Denise Pasqual (2007)
In the contemporary capitalist society violence assumes the status of an expression of the social relations that take place in the society and that occur in several places - the school being one of them. Until recently, the matter of school violence was treated within the boundaries of the school. Consequently, a large portion of the studies about violence in schools and whereabouts were focused on the teachers, students and their parents. With the introduction of the Estatuto da Criança e do Adolescente other public sectors such as Conselho Tutelar, Promotoria da Infância e Juventude and Delegacia de Proteção à Criança e ao Adolescente started to get involved with this issue. Therefore, we question how school violence has been perceived by these organizations. What are the expressions of school violence that come to them? The present study of school violence turned its attention to reveal the expression of this kind of violence from new and unprecedented sources of data. Hence, we present in this study expressions of school violence in the Santa Maria County from a point of view exogenous to the school. Our data sources were constituted by: documental analysis of inquiry transcripts from Delegacia de Proteção à Criança e ao Adolescente, semi-structured interviews with representatives from the three county Conselhos Tutelares and from Promotoria da Infância e Juventude of Santa Maria. The analysis of the collected data reveals that among several measures usually taken by the public schools and by parents the main one is the judicial characterization of school violence and school indiscipline. Furthermore, the demand for action from Conselho Tutelar agents in the school frequently comes along with an expectation for a punitive/repressive action rather than a protective one.